Kemampuan Pemecahan Masalah Matematis Siswa SMA berdasarkan Self-Directed Learning - Saputra, Andi; Zayyadi, Moh (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2024)
This research aims to analyze the mathematical problem-solving abilities of class X IPA 1 at SMA As-Suhuf Pamekasan in solving Systems of Linear Equations in Three Variables material through a Self-Directed Learning level. The type of research is descriptive research with a qualitative approach. Class X Science 1 students at As-Suhuf Pamekasan High School were chosen as research subjects. The test used in this research was SPLTV material with 2 questions in essay form. The results of the research based on the data analysis that has been carried out are: (1) students who have mathematical problem-solving abilities with a high level of self-directed learning can fulfill the five problem-solving indicators according to IDEAL, identify problems, define goals, explore possible strategies, anticipate outcomes and act, and look back and learn. (2) students who have mathematical problem-solving abilities with a moderate level of self-directed learning can fulfill the indicators of identifying problems, defining goals, and exploring possible strategies, that other indicators do not meet. (3) students who have mathematical problem-solving abilities with a low level of self-directed learning can fulfill the defined goal indicator and other IDEAL indicators do not fulfill it. Keywords:​ Mathematic problem solving, Self-Directed Learning